Kedudukan dan Fungsi Hadis dalam Islam - M. Jayadi (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
Al-Qur’an is Allah’s words revealed down to Muhammad saw to be spread to all menkind wherever they live. Whereas hadis is words uttered by Prophet. Al-Qur’an and hadis have a position as the main source of Islamic law/jurisprudence. Al-Quran constitute the first source, meanwhile hadis becomes the scound source. Hadis functions to explain qur’anic contents. Its explanation consist of bayaan al-tawkid, bayan tafsir, bayan al-tasyri’, and bayaan al-Nasikh.